Dois anos de Bolsa Verde: Seria a meta alcançável? - Jo\~ao Paulo Viana (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The Environmental Conservation Support Program - Green Grant (Bolsa Verde - BV) is focused on the poor rural people residing in priority areas defined by the Brazilian federal government, such as sustainable use protected areas, environmentally differentiated settlement projects and areas occupied by riverside communities whose agricultural practices are characterized by the systematic extraction of natural resources (ribeirinhos agroextrativistas). The BV is managed by the Ministry for the Environment, and is a component of the Brazil without Extreme Poverty Plan (Plano Brasil sem Miséria). To be eligible for benefits, families must meet the socioeconomic (monthly per capita income less than R 70) and environmental requirements (to live in an area that meets the requirements established by the Brazilian Forest Code in relation to native vegetation remnants, which must also possess a management plan or similar documents). The benefit corresponds to R 300 per quarter. After two years under way, the BV has reached 44,388 families in 24 states and 730 counties, paying just over R 69 million in grants. Beneficiaries of the state of Pará received 62.9% of BV total expenditures (approximately R 43.5 million), followed by Amazonas state (R 6.3 million or 9.1%), Bahia state (R 4.8 million or 7.0%), and Minas Gerais and Acre states (R 2.7 million or 3.9%, each) beneficiaries. Discounted the 306 families excluded from BV,the program reached 60.4% of its goal, which corresponds to 73,000 families by the end of 2014. This goal is feasible, provided there is an intensification of the efforts initiated in the second half of 2013 to find families that meet the criteria to enter the program. Suggestions for improvement of the BV are also presented and discussed.
Keywords: Q57; 330; Green Grant Program; Brazil Without Extreme Poverty Plan; protected areas; rural settlements; riverbank communities; payment for environmental services (PES); Amazon; biomes